Pathophysiological Links Between Myocardial Infarction and Anxiety Disorder, Major Depressive Disorder, Bipolar Disorder and Schizophrenia - Leong Tung Ong; Ching-Hui Sia (Biology)
There is increasing evidence demonstrating that psychiatric conditions elevate the risk of developing accelerated atherosclerosis and early-onset cardiovascular disease (CVD), including myocardial infarction (MI). Several mechanisms contribute to this observation. The dysfunction of the autonomic nervous system and hyperactivity of the hypothalamic–pituitary–adrenal axis in these patients contribute to the development of MI. Additionally, patients with underlying psychiatric disorders often have abnormal levels of anti-inflammatory and pro-inflammatory cytokines, which can lead to early vascular damage and subsequent atherosclerosis. Elevated PAI-1 levels, reduced tPA activity, and the decreased brain-derived neurotrophic factor (BDNF), influenced by coagulation and inflammation, may contribute to depression and its link to MI. Oxidative stress, marked by increased reactive species and impaired antioxidant defenses, is associated with cellular damage and has been consistently implicated in schizophrenia and bipolar disorder, potentially contributing to myocardial infarction. Finally, molecular genetic studies have indicated that psychiatric disorders and myocardial infarction may share potential pleiotropic genes. The interplay between the psychiatric conditions and myocardial infarction underscores the importance of integrated care approaches to manage both mental and physical health.